PROSPECTIVE DIRECTIONS FOR IMPROVING ADMINISTRATIVE LEGISLATION REGULATING INTERACTION BETWEEN LOCAL STATE ADMINISTRATIONS AND LOCAL GOVERNMENT BODIES (Bulletin of criminological association of Ukraine, 2023)
Attention is focused on the fact that the presence of gaps in administrative legislation, the norms of which regulate the interaction of local state administrations and local self-government bodies, is an objectively determined phenomenonThe need to revise the "State Regional Development Strategy for 2021-2027" currently in effect has been proven. The key steps to be taken in this direction are outlined.It is substantiated that adopting the concept of interaction between local state administrations and other state authorities means developing basic, fundamental ideas on which this joint activity will be based, formulating its priorities and development prospects. The factors that should be taken into account in the "Concept of improving the interaction of local state administrations with higher state authorities and local self-government bodies" are outlined
Keywords: improvement; administrative legislation; local state administrations; local self-government bodies